THE EFFECT OF MOBILIZATION ON THE INCIDENCE OF FLATULENCE IN POST SECTIO CAESAREA PATIENTS - Suhartini, Leni; Pardede, Tiarma Uli; Rahmatika, Cintya Putri; Widyastuti, Sri (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Sectio Caesarea (SC) surgery causes anxiety, postoperative pain, and feelings of fear, which causes late mobilization, resulting in complaints of flatulence.Objectives: To find out more about the effect of mobilization on the incidence of flatulence in post section caesarea patients. Method: This study used observational analytical studies, cross-sectional design, mothers who gave birth in January-February 2024, a population of 67 people; samples were taken by purposive sampling; mothers giving birth by SC (cito and elective). A sample of 55 respondents was obtained (SC ERACS 12 respondents, and non-ERACS 43 respondents).Result: The results found that there were as many as 13 respondents (81.3%) who experienced flatulence due to late mobilization. While in mothers who mobilized early, there was only 1 respondent (2.6%) who experienced flatulence. The results of statistical tests obtained a p value of 0.000, and it can be concluded that there is a difference in the proportion of flatulence of SC postoperative patients in mothers who do late mobilization and early mobilization (there is a significant effectiveness between mobilization and flatulence of SC postoperative patients). From the results of the analysis, the value of OR = 0.006 was also obtained, meaning that mothers who mobilize late have a 1 chance of experiencing postoperative flatulence compared to mothers who mobilize early.Conclusion: Early mobilization can reduce flatulence complaints in post-SC patients. Increasing education about the importance of postoperative mobilization to recover faster and avoid other complications that can arise due to postoperative SC, create interesting educational media to increase maternal knowledge.